An Open Microfluidic Chip for Continuous Sampling of Solute from a Turbulent Particle Suspension. Issue 5 (27th November 2020) - Shallan, Aliaa I.; Tavares, Yakini; Navvab Kashani, Moein; Breadmore, Michael C.; Priest, Craig
Abstract: High solids content complicates in situ analysis of chemical processing, biological suspensions, and environmental streams. In most cases, analytical methods require at least one pre‐treatment step of a small volume of sample before a particle‐free fluid can be analyzed. We have developed a continuous in situ sampler that can "sip" particle‐free solution from a turbulent high solids content stream (a slurry). An open microfluidic chip with an extended slit opening shields the internal laminar flow from the turbulence outside. Unlike other open chips, our chip does not require close proximity to a solid surface and operates in turbulent environments for hours without maintenance. Two applications are demonstrated: monitoring Fe III in a stirred slurry of mixed ore particles at high solids loading (4 %wt) and paracetamol tablet dissolution profiles for two different formulations. Abstract : An open microfluidic chip for aqueous phase sampling from high‐solids content turbulent slurries is demonstrated for mineral processing and pharmaceutical tablet dissolution slurries. The chip's 25 μm slit dampens turbulence in the outside fluid and allows partial exchange of inner and outer fluids, without entraining microparticles (>1 μm). The microfluidic flow profile, not size‐exclusion, enables the selective sampling of aqueous phase.